The Effectiveness of The Use of Diorama Teaching Aids on Students Interest and Learning - Alfhandy, Pramanda; Ismaun, Ismaun; Hikmah, Nur; Arham, Zul (Journal of Biological Science and Education, 2024)
Teaching aids are considered an important tool because they are used by educators in the delivery of education. The problem of facilities and infrastructure is considered an important issue in education, therefore it is necessary to update the existing facilities and infrastructure starting from updating school buildings to learning facilities. This research to determine the effectiveness of using teaching aids on the interest and learning outcomes of science in class VII students at Junior high school 9 Kendari. The type of research used is Quasi-Experimental Design research in the form of Non-Equivalent Control Class Design. Data collection methods are carried out through questionnaires and tests The population of this study was all seventh grade students of Junior high school 9 Kendari which amounted to 11 study class, with the research sample being class VII 10 which amounted to 27 students as the control class and class VII 8 which amounted to 30 students as the experimental class. Data analysis techniques used are descriptive and inferential data analysis techniques. From the research conducted related to the effectiveness of the use of diorama teaching aids obtained research results that in learning, there are differences in interest and learning outcomes between the control class that does not use teaching aids with experimental classes that use teaching aids. In addition, based on the N-gain test, the use of diorama teaching aids proved to be effective with the category of medium effectiveness level.Â Keywords: Effectiveness, Teaching Aids, Interest in Learning, Learning Outcomes, N-Gain